Mesiodistai crown dimension and tooth size ratio of the permanent dentition in CI. I malocclusion sample with spacing in the upper and Iowerjaws (Mustansiria Dental Journal, 2005)
A proper relationship of the total mesiodistal width of the maxillary dentition tothat of the mandibular dentition will favor an optimal post treatment occlusion, thepurpose of this study is to obtain information of the mesiodistal crown dentition and toothsize discrepancy in subject with Cl. I Angle malocclusion with spacing in the upper andlower arches. 30 pairs of dental casts were obtained (15 males, 15 females) weremeasured and analyzed, the results indicates no significant difference between right andleft sides, and non significant regarding tooth size analysis ( Bolton ratio) between malesand females, sexual dimorphism was found regarding mesiodistal crown dimension withgreater mean values for males